Crash Analysis of Bumper Assembly with Solver to Improvise the Design for Impact Tests (International Journal of Innovative Research in Engineering & Management, 2022)
Car bumpers can deform to absorb impact  energy. For static and modal analysis, a Benz vehicle bumper  was used. These analyses used a variety of bumper materials,  including glass-mat thermoplastic, aluminium alloy, and  mild steel with chromium plating (GMT). The majority of  modern cars have bumpers composed of PC/ABS, a material  blend of polycarbonate (PC) and Acrylonitrile butadiene  styrene (ABS). PETG, ABS, and TPU. The deformation and  strains grow as the car's speed rises from 55 km/hr to 90  km/hr, according to the static study. At a car speed of 75  km/h, the deformation and stress in the automobile bumper  were at their highest. It was found through the static analysis  that the stress values for PP material were lower.
Keywords: ABS; PETG; TPU; CATIA; Solid Works and stress analysis